An Undergraduate Syllabus with Research Orientation in Electronics and Communication Engineering - Puranchandra Rao, V. (Journal of Engineering Education Transformations, 2008)
An undergraduate syllabus for B.E.(Hons) which is research oriented covering Electronics and Communication Engineering is suggested. The syllabus is based on the present one for B.E./ECE of Anna University Chennai. This is intended for students with special aptitude for research within the same time frame of four years and such students comprise a ready channel for intake into R&D projects conducted in India and abroad. Also, in addition, a research qualification of Doctor in Engineering for such students will create a body of students well versed in research.